ILMU EKONOMI DAN PEMBANGUNAN INDONESIA (A DEVELOPMENT MANIFESTO FOR INDONESIA) - Mubyarto, Mubyarto; Bromley, Daniel W. (Journal of Indonesian Economy and Business, 2002)
Economic development must be thought of as a process in which a gradual and self-reinforcing evolution of institutions (âworking rulesâ) gets underway, all the while being informed and guided by the explicit purpose of: (1) encouraging economic growth; (2) enhancing the equality with which the benefits of that growth are shared; and (3) assuring that natural assets are not degraded in a manner that will compromise in the future either continued growth, or continued sharing of the benefits of growth. We see that institutions are central to growth, poverty alleviation, and sustainability. We also see that economic growth â increases in per capita GDP (or GNP) â is not sufficient unless it is also accompanied by a simultaneous and plausibly sustainable decrease in social inequality, and unless growth is not destructive of future growth and development.The process of economic development must incorporate three central ideas. These concepts concern ethics, law, and economics. Ethics concern collective perceptions of what is good and just not only in the present, but in terms of objectives to be pursued in the future. Law concern the application of the collective power to mediate and to enforce that ethical consensus â always with an eye to the future. Economics concerns the calculation of profit and loss predicated upon: (1) the ethical base of the nation state as a going concern; and (2) upon the legal foundations that give substance and content to the prior ethical foundations of that nation state.Keywords: Poverty Alleviation, Institutional Economics, Peopleâs Economy.